Students Self Regulated Learning in Numerical Methods Course using Computational Mathematics Teaching Materials - Baist, Abdul; Fadillah, Ahmad; Nopitasari, Dian (Malikussaleh Journal of Mathematics Learning (MJML), 2019)
Self regulated learning is a learning system applied in universities. Therefore, self regulated learning is needed by students in taking courses in college. Based on the results of previous studies found that students self regulated learning is still low. This study aims to improve students self regulated learning by using computational mathematics teaching materials in numerical method courses. The method used in this study is quasi-experimental with non-equivalent control group design. Result of this study shows that increasing students self regulated learning that using computational mathematics teaching materials is not better than students that not using the teaching materials.